Pengaruh Kegiatan Mewarnai Gambar Terhadap Kemampuan Motorik Halus Anak TK - Parman Parman; Treny Hera (Jurnal Sitakara, 2023)
The purpose of this study was to determine the effect of coloring pictures on fine motor skills of group A children at TK Al-Azhar 57 Jambi, with a total of 12 children and a sample of 8 children enrolled in the 2023/2024 school year. The observed indicators are using crayons correctly, adjusting the colors with the coloring pictures neatly and coloring doesn't go out of line. The results showed that there was an effect of coloring pictures on children's fine motor skills through statistical tests, namely the average test of 2 samples 2 parties in pairs or paired T test. Based on the results of the study it can be concluded that there is an effect of coloring pictures on fine motor skills of group A children at TK Al – Azhar 57 Jambi. Keywords: Picture Coloring Activities, Fine Motoric Skills, Early Childhood